Analysis of Lecturer Performance Effectiveness: The Role of Personal Branding, Social Media and Digital Products with Digital Economy Moderation in Private Universities in Tangerang - Imas Sukaesih; Asep Ferry Bastian; Mahmudin Mahmudin; Saidiah Saidiah; Ahmad Zaenur Rifa’i (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze lecturer performance effectiveness by examining the roles of personal branding, social media, and digital products, moderated by the digital economy. Specifically, it examines the direct effects of these variables and how the digital economy moderates their relationship with performance. A quantitative approach using a cross-sectional survey was applied. Data from 105 lecturers at private universities in Tangerang were analyzed with SEM-PLS. Findings reveal that personal branding and social media have a significant positive effect on performance. In contrast, digital products show a significant negative effect, potentially due to adaptation burdens and uneven digital literacy. The digital economy moderates these relationships selectively: it strengthens the effect of social media, weakens the effect of personal branding, and does not moderate the link between digital products and performance. These findings imply that universities should design structured digital literacy policies, strengthen academic branding programs, and establish supportive technology governance. Theoretically, this study contributes by integrating the digital economy as a selective moderator into the performance model and providing contextual evidence on digital adaptation in Indonesian higher education.